Pengaruh Corporate Social Responsibility dan Profitabilitas terhadap Nilai Perusahaan: (Studi Empiris Pada Indeks SRI-KEHATI yang Terdaftar di BEI) - Zulaika, Tatik; Sihombing, Grasella (Jurnal Akuntansi dan Governance Andalas, 2019)
This research purposes is to analyze the influence of Corporate Social Responsibility (CSR) and profitability as represented by Return on Equity (ROE) and Return on Investment (ROI) on the firm value. This research uses sample of SRI-KEHATI index in Indonesia Stock Exchange (IDX) during 2012-2016 period. Based on purposive sampling method, the total of research sample are 19 companies with 5 year observation. This research is a quantitative research using multiple regression analysis method. In the practice, statistic test is preceded by classical assumption test. The result of research show that partially and simultaneously the effect of CSR and profitability as represented by ROE and ROIon value of company is positif and significant. The implications of the study provide an understanding that in operational activities the company should not only seek profit but also must pay attention to its social responsibilities, while also providing benefits to stakeholders because the company can maintain and generate a positive corporate image which in the long run can increase the firm value reflected by stock price movements.